2011
DOI: 10.1080/13504851.2011.570702
|View full text |Cite
|
Sign up to set email alerts
|

The sustainability of trade balances in sub-Saharan Africa: panel cointegration tests with cross-section dependence

Abstract: This paper investigates the sustainability of trade balances in the Sub-Saharan African regions, using both the panel unit root (IPS) test proposed by Im et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…A number of studies have, on the contrary, shown the nonstationarity of CA or the lack of cointegration between exports and imports, thus suggesting the unsustainability of CADs and the violation of IBC. The studies supporting these findings include Tang () for Japan (1975:1–2004:11), Hamori () for G‐7 countries (1960–2005) and Hashiguchi and Hamori () for 37 countries in the Sub‐Saharan African region (1980–2006). Yet another set of studies has provided mixed evidence on the long‐run relationship between exports and imports and the implied sustainability of CADs.…”
Section: Perspectives On Ca: a Review Of The Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have, on the contrary, shown the nonstationarity of CA or the lack of cointegration between exports and imports, thus suggesting the unsustainability of CADs and the violation of IBC. The studies supporting these findings include Tang () for Japan (1975:1–2004:11), Hamori () for G‐7 countries (1960–2005) and Hashiguchi and Hamori () for 37 countries in the Sub‐Saharan African region (1980–2006). Yet another set of studies has provided mixed evidence on the long‐run relationship between exports and imports and the implied sustainability of CADs.…”
Section: Perspectives On Ca: a Review Of The Literaturementioning
confidence: 99%
“…The dominant support for cointegration between trade flows reinforces the intertemporal view, which suggests that the CADs are only short‐run phenomena and are sustainable in the long run. The results are consistent with several studies supporting the sustainability of CADs and the validity of IBC (Husted, ; Sawada, ; Wu, Fountas et al, ; Apergis et al, ; Wu, Chen et al, ; Arize, ; Irandoust & Ericsson, ; Herzer & Nowak‐Lehmann, ), but are inconsistent with those studies that suggest the unsustainability of CADs and the violation of IBC (Otto, ; Wickens & Uctum, ; Tang, ; Hamori, ; Hashiguchi & Hamori, ).…”
Section: Sustainability Of Cads: Some Policy Analyticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this paper is to analyze the sustainability of current accounts in African countries over the period 1980 to 2016, paying a specific attention to regional blocs, income levels and exchange rate regimes 1 (see Aizenman and Sun, 2010;Amba et al, 2017;Apergis et al, 2000;Baharumshah et al, 2005;Chang et al, 2012;Chen, 2011;Gnimassoun and Coulibaly, 2014;Hashiguchi and Hamori, 2012). African economies are generally concerned by a lack of credibility, which makes external financing more difficult and costly (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Factors accounting for this situation include a widening in fiscal deficits, slow growth, the slump in commodity prices, and exchange rate depreciations in the affected countries. Against this backdrop, the paper adopts a formal theoretical framework as well as recent cointegration techniques to analyze current account sustainability in 40 African countries (see Chang et al, 2012;Chen, 2011;Gnimassoun and Coulibaly, 2014;and Hashiguchi and Hamori, 2012). This paper differs from previous studies from at least four point of views: (i) since sustainability is a very sensitive question, it is analyzed both at panel as well as time series levels; (ii) to avoid misleading results heterogeneity and spatial analysis are accounted for; (iii) recent advances in econometric analysis are used in order to ascertain some influential results;…”
Section: Introductionmentioning
confidence: 99%